Pengaruh Kepemimpinan dan Pengawasan terhadap Produktifitas Karyawan pada PT. Trijaya Lestari - Iryadana, Mohamad Razab (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2023)
This study aims to determine the effect of leadership and supervision on employee productivity at PT Trijaya Lestari in Cikokol Tangerang, the method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing, the results of this study leadership have a significant effect on employee productivity is 46.9%, the hypothesis test is obtained t count > t table or (6.972 > 2.004). Supervision has a significant effect on employee productivity by 36.6%, hypothesis testing obtained t count > t table or (5.634 > 2.004). Leadership and supervision simultaneously have a significant effect on employee productivity with the regression equation Y = 10.202 + 0.426X1 + 0.333X2 and an influence contribution of 56.5%, hypothesis testing obtained F count > F table or (35.035 > 2.780).